1970
DOI: 10.1002/oms.1210030405
|View full text |Cite
|
Sign up to set email alerts
|

The ion kinetic energy spectra of some aromatic hydrocarbons

Abstract: The technique of ion kinetic energy spectroscopy has been applied to the study of the aromatic hydrocarbons benzene, toluene, naphthalene, 2-methyl naphthalene, biphenyl and anthracene. The method is illustrated by a complete study of naphthalene in which transitions of metastable doubly-and singly-charged ions are listed, including reactions in which singly-charged ions are formed by collision induced chargeexchange reactions of doubly-charged ions and by the double process of charge-exchange and metastable d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 5 publications
1
25
0
Order By: Relevance
“…KER carries valuable information concerning both the structures of the species involved and the energetics and dynamics of the reaction. 80,86 The amount of kinetic energy released can be calculated from the widths of peaks in ion kinetic energy spectra and the distance between the two charges at the moment of decomposition, estimated by 5,87 r Å D 14.40/KER eV can be used to infer information regarding the structures and geometries of precursor ions. 88,89 For example, the MIKE spectrum and B/E spectrum of the M 2C ion of indole 90 are shown in Fig.…”
Section: 61mentioning
confidence: 99%
See 1 more Smart Citation
“…KER carries valuable information concerning both the structures of the species involved and the energetics and dynamics of the reaction. 80,86 The amount of kinetic energy released can be calculated from the widths of peaks in ion kinetic energy spectra and the distance between the two charges at the moment of decomposition, estimated by 5,87 r Å D 14.40/KER eV can be used to infer information regarding the structures and geometries of precursor ions. 88,89 For example, the MIKE spectrum and B/E spectrum of the M 2C ion of indole 90 are shown in Fig.…”
Section: 61mentioning
confidence: 99%
“…at the intersection of two diabatic potential energy curves with interpartical separations of 2-6Å, corresponding to the so-called 'reaction window' resulting in a high probability for the net electron transfer for reactants at this range of distances. 110,115,127 This reaction has been studied via tandem mass spectrometry with both reverse-and forward-geometry sector mass spectrometers by Beynon and co-workers 86 It has been demonstrated that isomeric compounds can be readily distinguished by comparing their 2E mass spectra, even if their singly charged ion mass spectra are identical. 131 Although most of the work has been carried out with small dictations, multiply charged macro-ions, including C 60 and related fullerene compounds, have been subjected to studies of this kind.…”
mentioning
confidence: 99%
“…For example, it is useful in recognizing aromatic hydrocarbons from a mixture. 82 The selective scan can be performed on other types of tandem in space MS/MS instruments, for example, a triple quadrupole can be scanned so that Q3 (the second mass analyzer) is linked to the scan of Q1 (the first mass analyzer) in such a way that ions are transmitted through both analyzers if their mass/charge ratio increases by a factor of exactly two in the collision region (Q2) between the two analyzers. This is achieved by scanning Q3 at twice the rate of Q1 and this too has been demonstrated.…”
Section: Charge Changing Collisionsmentioning
confidence: 99%
“…However, in 1973 John Beynon and coworkers at the Department of Chemistry at Purdue would describe the instrumental development of the mass‐analyzed ion kinetic energy (MIKE) Spectrometer 52. The design of this instrument was based on earlier work by the same group on the ion kinetic energy (IKE) spectra of organic molecules53 and, although initially used to define the energetics of ion decomposition reactions, it was with this instrument combined with a soft ionization technique, such as chemical ionization, with which the Purdue team would, a few years later, prove the feasibility of direct mixture analysis54, 55 (shown below).…”
Section: Events From 1965 Through 1974mentioning
confidence: 99%
“…Within this 2‐year period there was a flurry of additional activity reported on promising applications of the new MS/MS technique, as indicated by McLafferty in his review in Accounts of Chemical Research 72. Of all these reports, those from the group of Cooks et al at Purdue,53, 54 utilizing a MIKE spectrometer (i.e. a reversed‐geometry double‐sector mass spectrometer), must be highlighted as they demonstrated for the first time full direct (nonchromatographic) analysis of mixtures via MS, both for positive and negative ions.…”
Section: Events From 1975 Through 1984mentioning
confidence: 99%